2012
DOI: 10.1111/j.1742-1241.2012.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the disclosure of MS diagnosis on anxiety, mood and quality of life of patients: a prospective study

Abstract: This first prospective study provides objective data showing that early disclosure of MS diagnosis improves both the patient's QoL and psychological well-being. In addition, the results seem to suggest that CIS disclosure does not lead to the same favourable effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…This result is in accordance with a recent study in which the authors demonstrated that 30 days after diagnosis disclosure, both anxiety and depression were significantly rated as better compared to the start screening, and this improvement remained stable over the two annual follow-ups (23). This result is in accordance with a recent study in which the authors demonstrated that 30 days after diagnosis disclosure, both anxiety and depression were significantly rated as better compared to the start screening, and this improvement remained stable over the two annual follow-ups (23).…”
Section: Discussionsupporting
confidence: 92%
“…This result is in accordance with a recent study in which the authors demonstrated that 30 days after diagnosis disclosure, both anxiety and depression were significantly rated as better compared to the start screening, and this improvement remained stable over the two annual follow-ups (23). This result is in accordance with a recent study in which the authors demonstrated that 30 days after diagnosis disclosure, both anxiety and depression were significantly rated as better compared to the start screening, and this improvement remained stable over the two annual follow-ups (23).…”
Section: Discussionsupporting
confidence: 92%
“…There may also be other benefits; one study indicated that a diagnosis of MS rather than a CIS epsiode reduces anxiety and increases quality of life and 'psychological wellbeing' of patients. 11 Neurologists may be better suited to the uncertainty of a CIS than patients, who may find understanding MS easier for themselves, family and colleagues. However, what evidence there is suggests that if all patients were treated at this point, some would receive long term unnecessary treatment with potential adverse effects which has both medical and financial implications.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be educated about the nature of their disease, particularly concerning the variable and unpredictable course of MS, what treatments are likely to achieve and potential adverse events they might experience [16]. Interestingly, early disclosure of an MS diagnosis has been shown to improve patients' quality of life and psychological wellbeing [64].…”
Section: Education and Open Communicationmentioning
confidence: 99%
“…The best approach to screening for depression in MS is to use the BDI with a cutoff score of 13 [62]. The Hamilton Rating Scale for Depression has been used in the Cognitive Impairment in Multiple Sclerosis study and the Chicago Multiscale Depression Inventory has been used in the Gruppo EmilianoRomagnolo Neurologi in Multiple Sclerosis study [63,64]. These scales can be used to measure the severity of depression and evolution of these symptoms in response to therapy, and also to differentiate between major depression and other depressive spectrum disorders which are common in patients with MS (e.g.…”
Section: Depressionmentioning
confidence: 99%